Unexpected Bone Metastases in 99mTc-Pertechnetate Scan of Recurrent Goiter. (January 2019) - Hoberück, Sebastian; Michler, Enrico; Seppelt, Danilo; Kotzerke, Jörg; Brogsitter, Claudia
Abstract : Abstract: A 68-year-old woman who underwent a thyroidectomy for bilateral goiter 20 years ago was referred to our department. The examination revealed a newly occurred thyroid nodule in the right central lobe. Unexpectedly the 99m Tc-pertechnetate scan revealed several extrathyroidal foci right-sided supraclavicular, beside a cold thyroid nodule in the right lower lobe. Consecutive surgery and histology confirmed the suspected diagnosis of follicular thyroid cancer with multiple bone metastases. Whole-body scintigraphy performed after the following radioiodine therapy indicated disseminated osseous metastases.